Response to neoadjuvant chemotherapy in operable breast carcinoma and conversion of modified radical mastectomy to breast conservation surgery, long term results: an Indian perspective - Sharma, Kunjan; Sharma, Dhruv; Gupta, Manoj; Seam, Rajeev; MInhas, S. S. (International Surgery Journal, 2017)
Background: This was a prospective study conducted in a tertiary care hospital over a period of one year w.e.f 01.09.06 to 31.08.07 and included 25 female breast cancer patients who were fine needle aspiration cytology proven. The objective of this study was to observe the response to neoadjuvant chemotherapy (NACT) in T1-T3, N0-N1, M0 patients and to determine the % of patients on whom breast conservation surgery could be performed. Majority of the patients were in 5th or 6th decades of life. Methods: Thorough clinical examination, bilateral mammography and ultrasound of the diseased breast was performed before administering CAF (cyclophosphamide, doxorubicin and 5-Fluorouracil) based NACT. Majority of the patients received three cycles of NACT. All patients tolerated the treatment well without any severe adverse effects. Results: Overall 84% of the patients showed response to NACT with 12% showing complete clinical regression of the primary tumour. The incidence of clinically negative axilla increased from 20% to 48% after NACT. The breast conservation surgery (BCS) rate increased from 12% to 64% after NACT. Conclusions: Of 16 patients who had undergone BCS, one patient had ipsilateral breast recurrence at four years and another one at six years of follow up; that proves the importance and success of BCS in carefully selected patients in our setup.